Лексико-семантичні трансформації в слов’янських перекладах текстів Лесі Українки як проблема міжкультурної комунікації - Приймачок, Оксана; Pryimachok, Oksana (Східноєвропейський національний університет імені Лесі Українки, 2018)
Статтю присвячено визначенню ролі лексико-семантичних трансформацій оригінального художнього тексту (твори Лесі Українки) при його перекладі близькоспорідненою російською мовою для досягнення ефективної міжмовної та міжкультурної комунікації. У роботі детально проаналізовано прийоми відтворення лексем з етнонаціональним змістом, слів-символів, українських реалій, фонової лексики, міжмовних часткових еквівалентів, омонімів і паронімів, лакун, експресивно- стилістичних компонентів. До найпоширеніших способів перекладу належать актуалізація російської лексеми з обмеженою сферою вживання, транслітерація (з елементами транскрипції), семантичні заміни (конкретизація, генералізація чи модуляція), антонімічне перефразування. Translation is a complex and multifaceted activity, in which decoding of the source text entails the interaction of different cultural codes. Artistic translation is one of the possible forms of intercultural communication at the verbal level. It is impossible to evaluate the role of the translated source text in the inter-language communication without an in-depth comparative stylistic analysis of its original version and foreign language translation (or translations). In this article the selected works by Lesia Ukrainka and their translations into Russian are used for such comparative analysis. Initially, any transcoding act is carried out at the level of the minimum translation-theme-word, which leads to a number of necessary interlanguage translation transformations. The more similar (genetically and structurally closer) the languages of the original and the translation are, the fewer, at first sight, there should be problems in reproducing verbal imagery of the source work. However, the lexical semantics of closely related languages has its own complexities. It is rather difficult to detect externally hidden semantic differences between lexical units. Trying to preserve the national cultural and stylistic features of the original, the translator has to consider all of these risks. It concerns, first of all, the words with ethnic-national content that do not have equivalents in the target language, word-symbols, background vocabulary, components with distinct expressive- stylistic coloring. Specialists in the Inter-Slavic translation must take into account the partial semantic equivalence of formally identical words and interlingual homonyms and paronyms. The linguistic, genre and rhythmic-intonational features of the original text result in different types of lexical-semantic transformations: transliteration (with elements of transcription), the replacement of words (with more specific or more generalized semantics) or compounding words (with compensated gaps), modulation of content (appearance of synonyms, periphrasis, common-root or thematically related words in translation). Often translators use an approximate translation that involves changes not only in the reference lexemes but also in the sequence of their appearance (or their interlingual synonyms, hyponyms, hyperonyms) in the context of the syntactic organization of expressions (the change of the communicative or modal type of sentences). This type of artistic literature translation takes into account grammatical accessory of common-root words, etc.
Lexico-Semantic Transformations in the Slavic Translations of Lesia Ukrainka's Texts as an Issue of Intercultural Communication
Keywords: перекладознавство; міжкультурна комунікація; етнономінація; безеквівалентна лексика; лексико- семантична трансформація; translation studies; intercultural communication; ethno-nomination; non-equivalence vocabulary; lexical-semantic transformation